Implementation of Marketing and Digital Marketing Project to Increase Sales of Griya Hijau Hidroponik Smes in Bandung City - Haryanto, Fara Tazkia Pramudya; Zaqiyah, Siti; Prasetyo, Andreas Recki (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Griya Hijau Hidroponik has not yet fully utilized digital marketing in increasing visibility on search engines, expanding marketing reach via social media, and increasing sales conversions of harvested produce. This project applies an interview method to find out the problems faced in marketing Griya Hijau Hidroponik and a questionnaire filling method to find out market conditions. Approach the problem using marketing and digital marketing capstone project methods. The implemented strategies include rebranding, website redesign, implementing on-page SEO through creating articles, implementing off-page SEO through creating Linktree, implementing content marketing through creating Instagram content, creating Google Search Ads, and activating sales through the Shopee marketplace. As a result, the project achieved 363 website visitors with a 1.94% ad click-through rate, a 13.8% increase in Instagram followers with 2.35% engagement, and a sales conversion improvement of 7.23% in the first month and 75.3% in the second month. This project offers relevant empirical data for academics and researchers to further analyze the link between digital marketing utilization and SME sales growth.